Pengaruh Variasi Latihan Dalam Peningkatan Kondisi Fisik (Keseimbangan, Kekuatan, Dan Kelentukan) Anggota Ekstrakurikuler Ju-Jitsu Dojo SMK Cendika Bangsa Kepanjen Kabupaten Malang - Yogam Prathista Hare Putra; Sapto Adi; Ardhiyanti Puspita Ratna (Universitas Palangka Raya, 2023)
This research aims to determine the effect of variations in training in the form of IPPON in improving the physical condition (balance, strength and flexibility) of members of the extracurricular Ju-jitsu Dojo SMK Cendika Bangsa Kepanjen, Malang Regency. The study design used was the one group pretest-posttest design. The population in this study was 20 people and sampling used purposive sampling technique and a sample of 17 respondents were obtained who participated in the research. The independent variable is IPPON, the dependent variable is physical condition (balance, strength and flexibility). The results of the paired t-test prove that the IPPON variable has no significant influence on the balance variable with a significance result of 0.818 (P Value > 0.05) with an average pre-test of 20.38 and post-test of 19.56, while in the strength variable there is significant influence with a significance result of 0.000 (P value > 0.05) with a pre-test average of 29.18 and post-test 35.12, for the flexibility variable there is also a significant influence with a significance result of 0.000 (P value > 0.05 ) with an average pre-test of 14.56 and post-test of 18.53.